2020
DOI: 10.3390/w12061780
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solution of the Two-Dimensional Richards Equation Using Alternate Splitting Methods for Dimensional Decomposition

Abstract: Research on seepage flow in the vadose zone has largely been driven by engineering and environmental problems affecting many fields of geotechnics, hydrology, and agricultural science. Mathematical modeling of the subsurface flow under unsaturated conditions is an essential part of water resource management and planning. In order to determine such subsurface flow, the two-dimensional (2D) Richards equation can be used. However, the computation process is often hampered by a high spatial resolution and long sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Comparing results obtained by the above three methods, it is demonstrated that the HIM method significantly increases calculation efficiency and accuracy. Moreover, by solving a 3D Richards' equation [41,42], the effectiveness of the HIM method in the nonlinear problem is verified.…”
Section: Introductionmentioning
confidence: 96%
“…Comparing results obtained by the above three methods, it is demonstrated that the HIM method significantly increases calculation efficiency and accuracy. Moreover, by solving a 3D Richards' equation [41,42], the effectiveness of the HIM method in the nonlinear problem is verified.…”
Section: Introductionmentioning
confidence: 96%
“…Richards' equation consists of a governing equation that is used to describe the water flow in subsurface porous media such as soil in unsaturated conditions [1]. It is continuously subjected to numerical investigation [2][3][4][5][6][7][8][9][10][11]. The modeling of water distribution using the equation has essential applications in climate science, agriculture and also ecosystem management [12].…”
Section: Introductionmentioning
confidence: 99%
“…Richards' equation consists of a governing equation that is used to describe water flow in subsurface porous media such as soil [1]. It is continuously subjected to numerical investigation [2][3][4][5][6][7][8][9].The modeling of water distribution using the equation has important application in climate science, agriculture and also ecosystem management [10]. Among many applications, Zeide [11] has reported the use of Richards' equation in the tree growth modeling prediction.…”
Section: Introductionmentioning
confidence: 99%